Analysis of Public Policy on the Management of Covid-19 Outbreak in Indonesia - Wardhana, Wisnu; Timur, Mutiara Kejora (Universitas Brawijaya, 2021)
This article discusses the efforts of the Indonesian government in dealing with cases of Coronavirus 19 (COVID-19) transmission. By understanding the government's efforts, measures, and policies formulated and implemented, the processing strategy can be evaluated. To analyze this, a deliberative policy analysis method is used, namely analyzing the narrative and arguments of the authorities in charge of understanding the implementation of decisions and policies, the writing of this article adopts a qualitative method, namely the descriptive analysis method. The data collection technology used is library research using books, journal articles, newspapers, online news, and websites of authoritative organizations. The important findings of this article are, first, the negative narrative and the slow response of the government to the spread of COVID-19. The narrative conveyed by political elites before COVID-19 entered Indonesia did not have a sense of crisis and would not threaten the speed of decision making. Second, there is weak coordination among stakeholders, especially between the central government and local governments. This coordinated synchronization results in unstable coronavirus control. Third, citizens are indifferent or disobedient to government calls. As a result, efforts to deal with it stopped because they did not receive support from the wider community. The combination of these three factors complicates the government's efforts to control the spread of COVID-19 in Indonesia.